2015
DOI: 10.1038/nm.3850
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of gastric cancer identifies subtypes associated with distinct clinical outcomes

Abstract: Gastric cancer, a leading cause of cancer-related deaths, is a heterogeneous disease. We aim to establish clinically relevant molecular subtypes that would encompass this heterogeneity and provide useful clinical information. We use gene expression data to describe four molecular subtypes linked to distinct patterns of molecular alterations, disease progression and prognosis. The mesenchymal-like type includes diffuse-subtype tumors with the worst prognosis, the tendency to occur at an earlier age and the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

86
1,810
12
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,734 publications
(2,041 citation statements)
references
References 46 publications
86
1,810
12
17
Order By: Relevance
“…3 Thus, after a decade of repeated failures of most targeted agents, except HER2, in showing survival benefits in gastric cancer, these positive trial results have opened a new era for exploring targeted agents for the treatment of gastric cancer. 4,5 Fibroblast growth factor receptors (FGFRs) are transmembrane tyrosine kinase receptors, and binding of ligands to FGFRs leads to activation of the downstream PI3K-AKT and MAPK-ERK pathways. 6 Dysregulation of the FGFR2 signaling pathway because of accumulation of epigenetic modifications and genetic alterations is associated with the development and progression of various cancers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Thus, after a decade of repeated failures of most targeted agents, except HER2, in showing survival benefits in gastric cancer, these positive trial results have opened a new era for exploring targeted agents for the treatment of gastric cancer. 4,5 Fibroblast growth factor receptors (FGFRs) are transmembrane tyrosine kinase receptors, and binding of ligands to FGFRs leads to activation of the downstream PI3K-AKT and MAPK-ERK pathways. 6 Dysregulation of the FGFR2 signaling pathway because of accumulation of epigenetic modifications and genetic alterations is associated with the development and progression of various cancers.…”
mentioning
confidence: 99%
“…11 In previous studies, the frequency of FGFR2 amplification varied from 3 to 9% depending on the testing methods. 4,5,[12][13][14][15][16][17][18] The prevalence rates also varied between countries-7% in the United Kingdom, 5% in China, and 4% in Korea-using the same FISH test analyzed in one core laboratory. 18 Nevertheless, the frequency of FGFR2 overexpression detection by immunohistochemistry ranged from 31% up to 51%-which were considerably higher than the incidence of FGFR2 amplifica tions.…”
mentioning
confidence: 99%
“…Similarly, no statistical significance was observed when the TLS gene signature was evaluated in an independent Asian Cancer Research Group (ACRG) cohort of GC patients (GEO accession GSE62254; Supporting Information Fig. S7) 34. Thus, mirroring the temporal development of TLSs in established disease in the gp130 F/F GC model, TLSs and an associated 3‐gene signature were also observed in human GC, albeit without prognostic value.…”
Section: Resultsmentioning
confidence: 98%
“…Gastric cancer driver genes were obtained from 3 sources: (1) 16 gastric cancer‐related driver genes from Catalogue of Somatic Mutations in Cancer (COSMIC) Cancer Gene Census(v78)31; (2) 175 driver genes of gastric cancer from the Integrative Onco Genomics (IntOGen) database32; (3) 108 significantly mutated genes (SMGs) and 26 somatic copy number alteration genes from previously published Whole Genome Sequencing (WGS) or Whole Exome Sequencing (WES) articles 4, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22…”
Section: Methodsmentioning
confidence: 99%
“…These studies have identified many driver genes, whose mutations confer selective growth advantage to tumor 11. Some of these driver genes are previously known cancer genes (eg, TP53 , ARID1A, and CDH1 ), while the others are new‐found significantly mutated genes in gastric cancer (eg, MUC6 , CTNNA2 , GLI3, and RNF43 ) 4, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22. Moreover, the copy number changes and characteristic mutational signatures also play important roles in gastric cancer development 4, 16, 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%